Analysis of Multiple Criteria Decision Making Method for Selection the Superior Cattle - Sumaryanti, Lilik; Nurcholis, Nurcholis (Universitas Nusantara PGRI Kediri, 2020)
The results of decision making play an important role in achieving a goal in solving certain problems. In the decision making process requires data or supporting evidence that can be used as a guide for the selection of solutions based on available alternatives, so as to produce choices that can increase productivity. MCDM method for the analysis of research data namely AHP, TOPSIS and SMART, the three methods are tested, because each MCDM method has a different way of working or algorithm, so it is necessary to experiment with certain cases. This study aims to determine the performance of the AHP, TOPSIS, and SMART methods with a case study of selecting superior female cattle breeds. The application of three MCDM methods for alternative analysts of prospective superior beef cattle based on testing to determine the accuracy of comparing the results/output of the system with expert recommendation solutions using a sample of 15 female cows that produce priority/ranking for superior beef cattle, shows that the performance of the three methods produces priority selection results the same, with 80% priority accuracy.